Castal Punishment in the Perspective of Islamic Law - Atika, Nur; Nuh, Ahmad; Salam, Abdul; Kappaja, Ismail (Family Law Study Program (Ahwal Syakhshiyah), Universitas Muhammadiyah Makassar, 2025)
This study aims to examine the application of chemical castration punishment to perpetrators of child sexual violence in Indonesia from the perspective of Islamic law. In Indonesia’s positive law, chemical castration is regulated in Law Number 17 of 2016 and Government Regulation Number 70 of 2020 as an additional penalty. The method used is a normative juridical approach with a qualitative research design. This study seeks to analyze the compatibility of chemical castration with the principles of Islamic law, focusing on whether it aligns with the maqashid al-sharia (objectives of Islamic law) and the core values of justice and fairness. The research findings suggest that chemical castration could be categorized as a form of takzir (discretionary punishment) in Islamic law, provided it does not conflict with the fundamental objectives of sharia, and that its implementation must adhere to the principles of proportionality and fairness. The research also critically assesses the broader implications of chemical castration, particularly from ethical, human rights, and legal perspectives. It delves into the ethical concerns of the medical profession regarding its implementation, highlighting the balance between upholding justice and respecting human dignity. Additionally, the study explores the views of contemporary Islamic scholars on the use of chemical castration as a punishment, assessing the debates surrounding its legitimacy in the context of Islamic jurisprudence. Ultimately, the study aims to provide a comprehensive understanding of the legal, ethical, and religious dimensions of chemical castration as a criminal penalty in Indonesia.